Determination of heavy metals in razor clam (solen sp.) at moyan and serpan - Faezah, binti Henry (Universiti Malaysia Sarawak (UNIMAS), 2008)
Razor clam (Solen sp.) was examined for concentration of heavy metals (Cd, Mn, Cr, Fe, and Hg) in two different parts, shells and tissues at Moyan and Serpan. The analysis of razor clams from both sampling sites showed wide distribution in concentration of heavy metals. Fe was recorded as the most abundant element in tissue while Mn was found higher in shell samples of razor clams followed by Cr, Cd and Hg at Moyan and Serpan. The concentrations of Cd and Cr in tissue and shell of razor clams exceeded the levels of Malaysian Food Act (1983) at both sampling sites. Concentration of Hg in tissue and shell was below the designated limit. There were no significant difference (P > 0.05) in the concentration of heavy metals in tissue and shell of razor clams between Moyan and Serpan.